National Security in the Conditions of the Russia-Ukraine War: Legal Regulation and Islamic Law Perspectives - Shkuta, Oleh; Leheza, Yevhen; Telelym, Iryna; Anosienkov, Anatolii; Yaroshak, Oleh (Al-Ahkam, 2024)
National security is an important condition for the functioning and development of individuals, societies, and the states, however, this security is threatened by war, and global military conflicts. This article aims to describe the national security threatened by the Russia-Ukraine war and all its effects from the context of legal regulation and Islamic law. This article is qualitative research with a historical and comparative approach. The study results concluded that Russia's full-scale invasion of Ukrainian territory, the formation of a new international military alliance, and the establishment of international cooperation to strengthen the security of the world community, were identified as innovative ways to develop international and global security. This is important to ensure national security in wartime conditions is maintained because security is a basic need that must be guaranteed in the context of national law, human rights, and Islamic law.